Chapter: 'Analysis of Breast Cancer Cell Invasion Using an Organotypic Culture System' from book: 3D Cell Culture: Methods and Protocols - Romana E. Ranftl (Methods in Molecular Biology, 2017)
Metastasis is the main cause of cancer patient mortality. Local tumor invasion is a key step in metastatic dissemination whereby cancer cells dislodge from primary tumors, migrate through the peritumoral stroma and reach the circulation. This is a highly dynamic process occurring in three dimensions that involves interactions between tumor, stromal cells, and the extracellular matrix. Here we describe the organotypic culture system and its utility to study breast cancer cell invasion induced by cancer-associated fibroblasts. This is a three-dimensional model that reproduces the biochemical and physiological properties of real tissue and allows for investigating the molecular and cellular mechanisms involving tumor and its microenvironment, and their contribution to cancer cell invasion. This system provides a robust, accurate, and reproducible method for measuring cancer cell invasion and represents a valuable tool to improve the mechanistic understanding of the initial steps in metastasis.